A new method for the reproducible development of aptamers (Neomers) - Cathal Meehan; Erika L. Hamilton; Chloé G. Mansour; Soizic Lecocq; Cole J. Drake; Yisi An; Emily Rodrigues; Gregory Penner (PLoS ONE, 2025)
The development of aptamers has been almost exclusively performed based on the SELEX method since their inception. While this method represents a powerful means of harnessing the in vitro evolution of sequences that bind to a given target, there are significant constraints in the design. The most significant constraint has been the reliance on counter selection on off-targets to drive specificity. Counter selection has not been as effective at driving aptamer specificity as the presence of immune tolerance, the capacity of the immune system to remove antibodies that bind to host targets, is for antibody development. This deficiency has constrained the commercial efficacy of aptamers to date. These limitations have been addressed with our design of a novel platform for aptamer identification. This new design is based on what we refer to as a Neomer library with sixteen random nucleotides interspersed with fixed sequences. The fixed sequences are designed to minimize the potential for hybridization, such that secondary structure is driven by the random nucleotides. The use of sixteen random nucleotides reduces the possible library sequences to 4.29 ×  10 9 . This enables the application of the same sequences to either the same target or different targets while maintaining a high level of structural diversity. In effect, this introduces the capacity for reproducibility in aptamer selection and an in-silico approach to replicating immune tolerance. We provide here an overview of the new method and a description of the performance of aptamers selected for interleukin 6 developed using this approach.